ECONOMIC EFFECTS OF THE APPLIANCE OF NEW TYPES OF MACHINES AND TOOLS FOR THE ARRANGEMENT OF SOILS IN SUNFLOWER PRODUCTION - Todorović, Sasa; Vasiljević, Zorica; Popović, Nikola (Economics of Agriculture, 2018)
The need of preservation and rational use of natural resources such is land requires the elimination of the usual practice of production and application of new technologies and new types of machines and tools. However, massive acceptation and successful application of new technologies and new types of machines and tools in practice requires certificates of manifestation the positive technical, technological and economic effects obtained through appropriate research. Bearing this in mind, the aim of this paper is to examine the economic effects of applying new technology and new types of machines and tools for the arrangement of soils surface and depth in sunflower production. In this sense, conducted economic analysis shows that a change in technology and application of new types of machines and tools in sunflower production is economically justified, given that there is a reduction of variable costs per kilogram of produced sunflower by 4.77%. The research and results obtained in this analysis represent only the first phase of research of the economic effects of application of new types of machines and tools in crop production (in this case in sunflower production). The results indicate the need to expand research to other important crops.